Influence of androgen deprivation therapy on glucose metabolism and ambulatory glucose profile - E. Yu. Grickevich; D. V. Skuridina; S. N. Perekhodov (Медицинский совет, 2021)
Introduction. Androgen deprivation, used to treat prostate cancer, leads to metabolic disorders, including glucose metabolism disorders. The timing of development and the characteristics of these changes have not been sufficiently studied. The expansion of the possibilities for assessing glycemia makes it possible to obtain changes in glucose.Objective. To study the dynamics of the effect of long-term androgen-deprivation therapy with gonadotropin-releasing hormone agonists (GnRH agonists) on the parameters of glucose metabolism and ambulatory glucose profile in patients with locally advanced prostate cancer (La PCa).Materials and methods. The study included 99 patients with La PCa receiving androgendeprivation therapy (ADT) with (GnRH agonists) for at least 12 months. The study of fasting plasma glucose (FPG) and glycated hemoglobin (HbA1c) levels was performed at baseline, after 3, 6 and 12 months of ADT, and constant self-monitoring of glycemia was recommended using portable glucometers. Flash glucose monitoring systems (FreeStyle Libre) were installed in ten patients with a detected increase in glycemia on the background of ADT, allowing them to obtain data on the ambulatory glucose profile (AGP).Results and discussion. Long-term ADT in patients with La PCa, regardless of baseline age, BMI, WC, was accompanied by an early, progressive deterioration in parameters of glucose metabolism. The proportion of patients with prediabetic FPG values after 12 months becames 66% according ADA criteria. We found that 12-month ADT changes the AGP: an increase area under the curve and postprandial glycemic levels, an increase in blood glucose variability with an increase in the CONGA index to 6.817 (p < 0.001).Conclusion. ADT by GnRH agonists in patients with La PCa is accompanied by a predisposition to early disorders of glucose metabolism with a high risk of rapid development of prediabetes regardless of baseline age, BMI, and WC. The AGP of patients is characterized by an increase in the total glycemic load, and glycemic variability.